MATERNAL AND PERINATAL COMPLICATIONS ACCORDING TO MATERNAL AGE : A SYSTEMATIC REVIEW - Noor Rosida, Yuna (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Maternal age of 40 years or more is associated with medical complications and more operative deliveries. Furthermore, very advanced maternal age is significantly associated with adverse perinatal outcome The aim: This study aims to show incidence, complications of advanced maternal age for maternal and perinatal Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 667 articles, whereas the results of our search on SagePub brought up 252 articles. The results of the search conducted for the last year of 2013 yielded a total 21 articles for PubMed and 7 articles for GoogleScholar. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: Understanding the incidence, complications of advanced maternal age for maternal and perinatal